2020
DOI: 10.2147/ott.s240973
|View full text |Cite
|
Sign up to set email alerts
|

<p>Construction and Analysis of a Long Non-Coding RNA-Associated Competing Endogenous RNA Network Identified Potential Prognostic Biomarkers in Luminal Breast Cancer</p>

Abstract: Purpose: To construct a competing endogenous RNA (ceRNA) topology network of RNAseq data and micro RNA-seq (miRNA-seq) data to identify key prognostic long non-coding RNA (lncRNAs) in luminal breast cancer, and validate the results by human luminal breast cancer samples. Materials and Methods: The RNA-seq data and miRNA-seq data of luminal A breast cancer in the The Cancer Genome Atlas (TCGA) database were downloaded and compared with those in the miRcode database to obtain lncRNA-miRNA relationship pairs. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…LncTM4SF1-AS1 in four GC cell lines, MKN28, AGS, MGC803 and SGC7901, was also significantly higher than that in normal gastric mucosa cells. The above results suggest that lncTM4SF1-AS1 was upregulated in GC, which is similar to that reported in the literature in NSCLC [ 9 ] and breast carcinoma [ 10 ]. In view of its upregulation in GC tissues and cells, this study selectively downregulated lncTM4SF1-AS1 in GC cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…LncTM4SF1-AS1 in four GC cell lines, MKN28, AGS, MGC803 and SGC7901, was also significantly higher than that in normal gastric mucosa cells. The above results suggest that lncTM4SF1-AS1 was upregulated in GC, which is similar to that reported in the literature in NSCLC [ 9 ] and breast carcinoma [ 10 ]. In view of its upregulation in GC tissues and cells, this study selectively downregulated lncTM4SF1-AS1 in GC cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…It is also a molecular marker of poor prognosis in patients [ 9 ]. RNA sequencing of breast carcinoma revealed that expression levels of TM4SF1-AS1 in breast carcinoma tissues were higher than those in adjacent tissues [ 10 ]. However, the role and mechanism of TM4SF1-AS1 in GC are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…OIP5-AS1 was higher in breast tumors compared with normal breast tissue and high OIP5-AS1 correlated with tumor size, LN metastasis, and tumor grade [ 81 ]. Another study found that OIP5-AS1 expression correlates with a high risk of worse outcomes for luminal BC patients [ 82 ]. Knockdown of OIP5-AS1 in MDA-MB-231 cells inhibited xenograft tumor growth in BALB/c nude mice, validating its oncogenic activity in vivo [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that a variety of lncRNAs are dysregulated in breast cancer and they have an effect on the oncogenesis, progression, and metastasis of breast cancer. 27–29 Continued studies on the role of breast cancer-related lncRNAs will lead to an understanding of the mechanisms that underly breast cancer pathogenesis and identity new targets for therapy. In the present study, we explored the role of LINC00504 in regulating oncogenesis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%